HnRNPC regulates cancer-specific alternative cleavage and polyadenylation profiles. Issue 14 (31st May 2019) - Fischl, Harry; Neve, Jonathan; Wang, Zhiqiao; Patel, Radhika; Louey, Alastair; Tian, Bin; Furger, Andre
Abstract: Alternative cleavage and polyadenylation (APA) can occur at more than half of all human genes, greatly enhancing the cellular repertoire of mRNA isoforms. As these isoforms can have altered stability, localisation and coding potential, deregulation of APA can disrupt gene expression and this has been linked to many diseases including cancer progression. How APA generates cancer-specific isoform profiles and what their physiological consequences are, however, is largely unclear. Here we use a subcellular fractionation approach to determine the nuclear and cytoplasmic APA profiles of successive stages of colon cancer using a cell line-based model. Using this approach, we show that during cancer progression specific APA profiles are established. We identify that overexpression of hnRNPC has a critical role in the establishment of APA profiles characteristic for metastatic colon cancer cells, by regulating poly(A) site selection in a subset of genes that have been implicated in cancer progression including MTHFD1L .